Mini Riset Sebagai Metode Pembelajaran Sosiologi Materi Permasalahan Sosial Di Masyarakat - Setiawan, Nurman (MAN 4 Kota Pekanbaru, 2022)
The lack of variety of learning methods and models makes sociology one of the subjects often considered boring. Because of this, students' interest in learning is minimal, and their learning achievement is also low. This study aims to look at implementing the mini-research method as an alternative method of learning sociology, especially on social issues. The method used is descriptive qualitative by analyzing various literature related to the topic and the author's implementation. The application of this method indicates an increase in students' interest in learning which can be seen from their enthusiasm for participating in learning. Furthermore, understanding of the material is also increasing, as evidenced by the evaluation results, which show good grades. Finally, this study concludes that the Mini Research method can be an alternative method of learning sociology, especially on social issues